Penatalaksanaan Pengobatan Tuberculosis Paru - Juli Andri; Henni Febriawati; Yusuf Randi; Harsismanto J; Asih Dewi Setyawati (Jurnal Kesmas Asclepius, 2020)
The purpose of this study was to see how the management of pulmonary tuberculosis treatment. This research uses a qualitative approach. The results showed that 1 in 3 tuberculosis patients did not comply with tuberculosis treatment in the working area of the Sukamerindu Public Health Center, Bengkulu City. Factors that support treatment non-compliance are the lack of knowledge of tuberculosis treatment guidelines. In conclusion, patients who do not comply are caused because they feel he is already healed and are lazy to take more medicine at the Sukamerindu Health Center, PMO already understands his duties as a PMO. Keywords: Compliance with Medication, Drug Giver, PMO, Pulmonary Tuberculosis